Upaya Peningkatan Keaktifan Belajar Siswa Melalui Model Pembelajaran Problem Based Learning Tema 9 Benda-benda Di Sekitar Kelas V SD Negeri Tonoboyo 2 Kabupaten Magelang - Febri Suci Ramadhani (Continuous Education: Journal of Science and Research, 2022)
This research is motivated by the lack of teachers in using learning models that attract the attention and understanding of students during learning, and teachers pay less attention to student learning activities in the learning process, so that students in the learning process play a lot and disturb their classmates. This study aims to determine the increase in student learning activity through the problem based learning model in Class V at Elementary School State Tonoboyo 2, Magelang Regency. This study uses a type of classroom action research with the subject of 10 fifth grade students of Elementary School State Tonoboyo 2, Magelang Regency. There are 4 stages of procedures carried out in this study, namely planning, implementing actions, observing, and reflecting. In collecting data, researchers used the method of observation and documentation. The data analysis technique used is descriptive qualitative analysis. Based on the results of the study, it can be concluded that there is an increase in the implementation of learning with the problem based learning model from cycle I to cycle II by 17.5% and student learning activity by 17.9%. During the activity process of each cycle carried out, the activity of students in the learning process increased every meeting and students' attention to the material being taught increased, and the enthusiasm of students in participating in learning was very good.